Work Productivity and Activity Impairment in Irritable Bowel Syndrome (IBS): A Multifaceted Problem. (October 2018) - Frändemark, Åsa; Törnblom, Hans; Jakobsson, Sofie; Simrén, Magnus
Abstract : OBJECTIVES: Patients with irritable bowel syndrome (IBS) are more likely to be both absent from and impaired at work compared to non‐IBS patients. We investigated the impact of IBS on work productivity and activity impairment and the relationship to disease specific and general health measures. METHOD: In total, 525 patients with IBS completed questionnaires assessing work productivity and activity impairment, IBS symptom severity, IBS‐related quality of life and GI‐specific anxiety. In addition, 155 of the patients completed questionnaires assessing severity of somatic symptoms, depression, anxiety and fatigue. Uni‐ and bivariate analyses were performed, as well as linear regression to determine factors independently associated with the work productivity and activity impairment measures. RESULTS: Of employed patients, 24.3% reported absenteeism and 86.8% reported presenteeism because of their IBS. With increasing severity of IBS symptoms and GI‐specific anxiety, higher degrees of work impairment were seen. Work productivity impairment in IBS was also associated with low quality of life. GI‐specific anxiety was independently associated with absenteeism ( R 2 = 0.23; p < 0.05), IBS‐symptom severity and general fatigue with presenteeism ( R 2 = 0.40; p < 0.05), IBS‐symptom severity, general fatigue and GI‐specific anxiety with overall work loss ( R 2 = 0.50; p < 0.05), and IBS symptom severity and somatic symptoms with activity impairment ( R 2 = 0.38; p < 0.05). CONCLUSION: Work impairment is a substantial problem in patients with IBS. A combination of IBS and somatic symptom severity, fatigue and psychological factors influence patients' ability to be present, active and productive at work. Based on this, a multidimensional treatment approach for patients with IBS seems logical.